IMPLEMENTATION OF VISUAL CRYPTOGRAPHY TECHNIQUE ON SQUARE BW SECRET IMAGES - Stephanie I. Pella; M. J. Pella (Jurnal Media Elektro, 2012)
The advance of computer security technology has led to the invention of many cryptography algorithms. Visual Cryptography is a cryptography technique that needs no cryptographic computation in decoding. To encode a secret image, the image is encrypted to several transparent shares. In order to retrieve the secret image shares are stacked on top of each other. This paper describes a technical implementation of this algorithm on a square black and white image for VC2,2 Scheme and VC3,3 Scheme. The result shows that the model works well with an image that contains text.